Parenting researchers—an invisible divide. (17th June 2020) - Roberts, Luc; Kothe, Ute; Wieden, Hans‐Joachim
Abstract : The corona pandemic is an opportunity to rethink and revamp the academic career and reward system that consistently disadvantages parenting scientists and women.